DEVELOPMENT OF SMART NUTRITION GAMIFICATION MEDIA TO IMPROVE NUMERACY LITERACY IN ELEMENTARY SCHOOLS - Ratri Nuryani Qudwatullathifah; Nurhadiansyah Nurhadiansyah; Florentina Bete; Nazma Amatul Qudus (Program Studi PGSD Universitas Flores, 2025)
Nutritional problems and low numeracy literacy among elementary school students in Indonesia remain critical challenges that affect both academic achievement and health-related behaviors. This study aimed to develop a digital gamification-based learning media called Smart Nutrition to improve students’ numeracy literacy in the context of the Free Nutritious Meal Program. The research employed the ADDIE development model, consisting of analysis, design, and development phases, followed by expert validation. The media content integrated calorie counting, portion estimation, and interpretation of nutrition labels into gamified missions featuring points, badges, levels, leaderboards, and instant feedback. Validation by experts in media and content resulted in an average score of 94%, indicating that the product was categorized as very valid. These results suggest that the Smart Nutrition prototype is a feasible and innovative digital learning tool that combines gamification and nutrition-based numeracy content, and is ready for further trials on practicality and effectiveness in classroom settings.